2021
DOI: 10.1007/jhep06(2021)024
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement negativity and replica symmetry breaking

Abstract: Since the work of Ryu and Takayanagi, deep connections between quantum entanglement and spacetime geometry have been revealed. The negative eigenvalues of the partial transpose of a bipartite density operator is a useful diagnostic of entanglement. In this paper, we discuss the properties of the associated entanglement negativity and its Rényi generalizations in holographic duality. We first review the definition of the Rényi negativities, which contain the familiar logarithmic negativity as a special case. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 60 publications
3
75
0
Order By: Relevance
“…However, we must add that the connection between EWCS and logarithmic negativity was recently called into question by[11]. In particular, the derivations of[10] were shown to not apply for bulk solutions that break the replica symmetry.…”
mentioning
confidence: 99%
“…However, we must add that the connection between EWCS and logarithmic negativity was recently called into question by[11]. In particular, the derivations of[10] were shown to not apply for bulk solutions that break the replica symmetry.…”
mentioning
confidence: 99%
“…This is in contrast to the holographic theories where the negativity is proportional to the mutual information for all times, i.e. E = 3I/4 [20] or E = I/2 [30]. Moreover, in the decompactification limit (increasing the system and subsystem sizes properly) the rate of decreasing of logarithmic negativity becomes more sharply which it might be the sign of sudden death of entanglement before the trivial (finite size effect) revival.…”
Section: Ln Vs Mutual and 1/2-rényi Mutual Informationmentioning
confidence: 73%
“…Although, it has been recently argued that there might be counterexamples for this duality; for more details see[30] 4. Recently, OEE for Lifshitz scalar theories has been studied in[31] where it has been shown that it can be negative.…”
mentioning
confidence: 99%
“…So long as the minimal extremal surface homologous to U is unique, and we restrict to n < O(1/G N ), this remains true in the stateψ. 10 Given this, the additional qubits do not enter E U in the perturbed state, so do not contribute their entropy to S(U )ψ. On the other hand, by the unitarity property the message is localized to V 1 ∪ U , so the entropy of the additional n qubits do contribute to S(V 1 U )ψ.…”
Section: Jhep09(2021)042mentioning
confidence: 99%
“…In the context of the AdS/CFT correspondence, the Ryu-Takayanagi formula [1] and its covariant generalizations [2][3][4][5] have deepened our understanding of how geometry and gravitational physics can be recorded into quantum mechanical degrees of freedom. Other proposals relate a variety of bulk geometric quantities to boundary entanglement, see [6][7][8][9][10] for an incomplete listing. In all cases, boundary correlation is related to bulk spacelike surfaces.…”
Section: Introductionmentioning
confidence: 99%